Cirrhosis liver and Hepatitis B and C Virus Infection - Rehman, Masood ur; Farooqi, Javed Iqbal (Journal of Postgraduate Medical Institute, 2011)
a retrospective study was conducted in the department of MedicineLRH, Peshawar from June 1998 to June 2000, to find out the relative frequency of HBV and HCV infection in patients of liver cirrhosis. One hundred and ten patients were analyzed. Anti-HCV was positive in 59% patients. HBsAg was positive in 32% patients. Both were positive in 3% patients. Both were negative in 6% patients. We conclude that HCV is a leading cause of cirrhosis in our patients of liver cirrhosis, followed by HBV, both account for about three fourth of the total patients of liver cirrhosis.